Security under construction : a Bourdieusian approach to non-state crisis centres in northwest Russia - Stuvøy, Kirsti (Universitetet i Tromsø, 2009)
This study examines the work of non-state crisis centres for women in Northwest Russia by asking “How do non-state crisis centres for women in Northwest Russia produce security?” The work of Pierre Bourdieu contributes to an analytical approach that illustrates security practices in regard to this context. On the basis of interviews conducted with crisis centre representatives, Moscow-based national women’s groups and Norwegian collaborators in Northern crisis centre work, this analytical approach is used to explain the dynamics of the local security production. Three thinking tools in Bourdieu’s work, field, capital and habitus are used in this study. The concept of field defines an analytical framework characterized by the relations between the crisis centres and local stakeholders as well as between the crisis centres and their clients. The concepts of capital and habitus depict the objective constraints and subjective aspects relevant to the local security production. In result the study illustrates that crisis centres in Northwest Russia manoeuvre in the field on the basis of their social capital. This implies in this context that security production is ad hoc and personalized. Most centres do not offer a physical shelter but nonetheless provide a discursive space and an information hub for victims’ process of re-describing self and thus recreating a situation of security. This novel analytical approach to examining local security practices and the work of non-state crisis centres displays a de-militarized understanding of security. This conceptualization of security reflects human security and its concern with people-centred security. A weakness in human security research however concerns empirical study, and this is addressed in this case study of non-state crisis centres in Northwest Russia. The study contributes by making visible ongoing practices of security production that define people’s security reality and thereby challenges pre-conceived conceptions of security and its connection to the use of ...